Orbital forming of tailored blanks with two-sided local material thickening - Hildenbrand, Philipp; Lechner, Michael; Vogel, Manfred; Herrmann, H.; Merklein, Marion (International Journal of Advanced Manufacturing Technology, 2018)
Economic and ecological demands like saving resources and improved material efficiency can be achieved by the application of process adapted semi-finished parts, so-called tailored blanks, for the manufacturing of for example gearings or synchronizer rings. Functional components require the locally restricted distribution of an adequate amount of material at defined positions in order to properly form functional elements like gearings or carriers. As these elements can be formed on one or both sides of the component, an appropriate material provision on one or both sides of the sheet metal is necessary. Having material thickenings on two sides lead to the interaction between both sides for example with regard to the maximum die filling. One process to produce tailored blanks is orbital forming. While manufacturing these tailored blanks with a local material thickening on one side of the sheet metal is state-of-the-art, the realization of these tailored blanks on both sides has not been investigated yet. In this paper, the results regarding the manufacturing of tailored blanks with a two-sided local material thickening will be presented for the first time. By analyzing three different tailored blank geometries, the influence of the interactions of two-sided material thickenings will be investigated. The results will be evaluated in terms of the resulting geometrical and mechanical properties.
LFT Import::2019-07-29 (2310)
Keywords: Forming; Orbital forming; Sheet-bulk metal forming; Tailored blank